A stable bis(methylene)-λ4-selane with a >CSeC< bond containing Se(iv). Issue 57 (27th June 2019) - Sugamata, K.; Urao, Y.; Minoura, M.
Abstract : Bis(methylene)-λ 4 -selane1, which represents a new class of heteroallenes, was synthesized and isolated as a stable purple crystalline solid. Abstract : Bis(methylene)-λ 4 -selane1, which represents a new class of heteroallenes, was synthesized and isolated as a stable purple crystalline solid. X-ray crystallographic analysis revealed a bent allene-type structure with pseudo C 2v symmetry and a bent CSeC moiety that contains a 3-center-4-electron π-bond. The NMR spectrum of1 shows compelling evidence for a slow rotation of the SeC moieties at room temperature. The 77 Se NMR spectrum of1 contains one signal in the region characteristic for Se(iv ) compounds.